The Framingham Heart Study and the epidemiology of cardiovascular disease: a historical perspective - Mahmood, Syed S; Levy, Daniel; Vasan, Ramachandran S; Wang, Thomas J (The Lancet (British edition), 2014)
On Sept 29, 2013, the Framingham Heart Study will celebrate 65 years since the examination of the first volunteer in 1948. During this period, the study has provided substantial insight into the epidemiology and risk factors of cardiovascular disease. The origins of the study are closely linked to the cardiovascular health of President Franklin D Roosevelt and his premature death from hypertensive heart disease and stroke in 1945. In this Review we describe the events leading to the foundation of the Framingham Heart Study, and provide a brief historical overview of selected contributions from the study.